The Relationship between Motivation and Job Performance among Employees in the Manufacturing Companies - Rodzalan, Shazaitul Azreen; Noor Ghaney, Nur Azlan (Research in Management of Technology and Business, 2022)
Job performance is crucial aspect in ensuring an organizational success. However, employee performance are said not up to the standard, since the outbreak of pandemic Covid-19. Employees are less motivated to perform their work to meet up with the organization standard. Thus, this study aims to identify the level of the motivation among and level of job performance in the manufacturing sector. This study also aim to examine the relationship between motivation and job performance the manufacturing companies. This research was focused on the manufacturing companies in Selangor as this state is one of the biggest manufacturing area in Malaysia.  To collect the data, the questionnaire has been distributed to employee who work in manufacturing companies in Selangor. Results shows that there is a moderate level of job performance and extrinsic motivation among employees in manufacturing companies, while intrinsic motivation was reported at high level. Besides, there is a significant relationship between motivation and job performance among employees in manufacturing companies. Results of this study will have implications to the stakeholders, mainly to employees and top management in the manufacturing companies.